PHYSIOTHERAPY MANAGEMENT FOR CARPAL TUNNEL SYNDROME: A CASE STUDY - Ni'mah, Dita Nurul; Naufal, Adnan Faris; Wijayaningsih, Anteng (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Carpal tunnel syndrome (CTS) is the most common neuropathy caused by compression of the median nerve in the carpal tunnel, which can cause symptoms such as pain, tingling, and numbness,the prevalence is 5.8% in adult women and 0.6% in men. The purpose of this study was to determine the effectiveness of a physiotherapy program using manual therapy, and exercise therapy to reduce pain and increase functional activity in patients with Carpal Tunnel Syndrome (CTS). Case Presentation: Mr. H complained of tingling in his left hand from the wrist to the 4th finger and sometimes felt pain. Complaints are exacerbated at night so that it is difficult to sleep. Mr. H has difficulty driving a motorbike or car, buttoning clothes, opening bottles, and doing activities requiring the left hand. Management and Outcome: The patient attended therapy four times once a week for four weeks with a physiotherapy program manual therapy, stretching exercises and strengthening exercises. Patients were evaluated using the Numerical Rating Scale (NRS), Manual Muscle Testing (MMT), and Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ). Conclusion: Physiotherapy management in the form of manual therapy, stretching exercises and strengthening exercises performed once a week for four weeks can reduce pain and increase the functional activity.